A new data acquisition and processing system for UAVSAR - Lim, Chot Hun; Lim, Chee Siong; Chua, Ming Yam; Chan, Yee Kit; Lim, Tien Sze; Koo, Voon Chet (2011)
Synthetic Aperture Radar (SAR) is widely known as a high resolution imaging system in microwave remote sensing. Large number of frequency-modulated received echoes must be acquired in real time. A typical SAR data acquisition unit (DAQ) involves high speed analog-to-digital conversion, front-end pre-processing, and data recording. Subsequent processes consist of computationally intensive digital signal processing for image formation. In this paper, an efficient data acquisition and SAR processing method is proposed. It is based on a modified discrete Fourier Transform algorithm, which requires lesser system's computational load as compared to conventional Fast Fourier Transform. The proposed system has been implemented on an UAVSAR (Unmanned Aerial Vehicle SAR) and the flight tests have shown promising results for real-time imaging.